2009
DOI: 10.1016/j.genhosppsych.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and anxiety in musculoskeletal pain patients with and without depression

Abstract: Objective Determine if psychosocial stress and anxiety were associated with depression severity in primary care patients with chronic musculoskeletal pain. Method A cross-sectional sample of 500 primary care patients with musculoskeletal pain (250 with depression and 250 without depression) were assessed for anxiety, psychosocial stress, depression severity, and demographics. The depressed and nondepressed participants were compared using t-test and chi-square analyses. Multiple linear regression analyses ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 41 publications
1
50
1
5
Order By: Relevance
“…Furthermore, a substantial body of literature has demonstrated that psychosocial factors are strong predictors of response to medical interventions, including surgeries and injections directed toward pain relief [3,4]. Moreover, psychosocial factors are also strong predictors of pain, function, and quality of life among people with chronic pain [517]. The biopsychosocial model has emerged as the most comprehensive model in the field of pain management [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a substantial body of literature has demonstrated that psychosocial factors are strong predictors of response to medical interventions, including surgeries and injections directed toward pain relief [3,4]. Moreover, psychosocial factors are also strong predictors of pain, function, and quality of life among people with chronic pain [517]. The biopsychosocial model has emerged as the most comprehensive model in the field of pain management [18].…”
Section: Introductionmentioning
confidence: 99%
“…1 Women are two to nine times as likely as men to acquire varied pain conditions, 2–5 and gynecologic and many pelvic pain conditions are female-specific. 68 Chronic pain is associated with lower quality of life, 9 increased psychological distress, 1014 and substance use behavior 1518 —factors that are prevalent in the female offender population. 1924 Incarcerated women generally have more medical comorbidity than incarcerated men, suggesting greater likelihood for chronic pain.…”
mentioning
confidence: 99%
“…2017; 19(4):e45084. 5 function (33). Anxiety and depression are factors stimulating the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%